Pemanfaatan Ruang Otonomi Daerah Dalam Pengelolaan Pendidikan Agama Islam (PAI): Studi Kasus Kabupaten Kubu Raya - Abdul Lutfy; Usman Usman; Nor Fadhilah (STIKes Ibnu Sina Ajibarang, 2026)
This study was motivated by the existence of regional autonomy, which provides opportunities for local governments to contribute to the management of Islamic Religious Education (IRE), although the primary authority over religious education remains under the Ministry of Religious Affairs. Kubu Raya Regency, as a region characterized by a religious society, possesses significant potential for developing IRE policies that are responsive to local needs. This study aims to analyze the implementation of IRE policies within the framework of regional autonomy, identify supporting and inhibiting factors, and formulate strategies for strengthening IRE policies in Kubu Raya Regency. The research employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that the implementation of IRE policies has been carried out relatively well through synergy among schools, communities, local governments, and the Ministry of Religious Affairs. Supporting factors include a religious social environment, teachers’ commitment, and support from schools and local governments. Meanwhile, the challenges encountered include limited human resources, suboptimal inter-institutional coordination, and inadequate facilities and infrastructure. The study implies the importance of strengthening institutional synergy, enhancing teacher competence, developing local wisdom-based programs, and promoting innovative learning approaches to improve the quality of IRE sustainably.